Analisis Tokoh Suhita Pada Novel Hati Suhita : Kajian Feminisme Marxis - Sa’adah Fuji Astutik; Ahmad Ilzamul Hikam (Fonologi: Jurnal Ilmuan Bahasa dan Sastra Inggris, 2025)
This study aims to analyze the character of Alina Suhita in the novel Hati Suhita by Khilma Anis using the Marxist feminist theory approach. The main focus of this study is to reveal how the patriarchal system and social class structure influence the position and experiences of female characters in the novel. The study uses qualitative methods with text-based content analysis techniques and a hermeneutic approach to interpret the meaning contained in the narrative. The results of the analysis show that the character Suhita experiences three main forms of oppression: stereotypes, subordination, and marginalization. These three forms reflect how women in a patriarchal society are negatively constructed, positioned lower than men, and excluded from public spaces and decision-making. However, Suhita also shows resistance to dominant structures through her intelligence, education, and active role in the Islamic boarding school. In the context of Marxist feminism, Suhita is a representation of women who experience double exploitation both as women and as part of a marginalized social class but also have the potential to be agents of change. This study emphasizes that literature can be a medium for understanding power relations in society as well as a tool for criticizing ongoing gender and economic inequality.